A PENGEMBANGAN KAWASAN RUMAH SUSUN TERPADU TIGA BERLIAN PEGAMBIRAN KOTA CIREBON - Agustine, Reffiyanti (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2022)
ABSTRACT The rapid economic growth in the city of Cirebon makes migration from outside the city of Cirebon as of Cirebon, Kuningan, Indramayu, Majalengka and Cirebon city is a center for economics and business in the northeast region of West Java. Vertical development in the form of blocks of flats in the city of Cirebon is an alternative to meet the housing needs of the industrial workers in the city of Cirebon. This study aims to vertical housing construction industry workers. In this study using the method of analysis Strength Weakness Opportunities Threats (SWOT) analysis to determine the feasibility of the location for conversion to flats integrated questionnaire method to determine the interest of industrial workers to stay in the bunk house and integrated planning for building a building of 5 (five) floor designed with sketchUp and calculated with manual calculations based SNI Building Planning and ETABS application for comparison. The results of his research is the construction of flats four (4) of the building with an area of ​​7,410 square meters with every building there are 96 spacious units with each unit of 36 square meters. Keywords: Integrated Housing Area Development, SWOT Analysis, Structural Analysis.